Trends of vocational education and training research in building construction engineering - Ramadhan, M. Agphin; Handoyo, Santoso Sri; Cahyati, Winda (Universitas Negeri Padang, 2021)
Research that has been done by building engineering students as a thesis tends to choose a theme that has been widely researched before. This research aims to find out the trends of vocational education research in the field of engineering building including trends of theme research and trends of methodology research. This research used descriptive quantitative research methods with a library research approach. Data collection techniques using documentation. Data analysis techniques are used in content analysis. The results of this study show the trends that have occurred in vocational education research in the field of building engineering in 4 universities, then obtained the trend of vocational education research themes and research methodology trends: 1) The theme of vocational education research in the field of building engineering is in high demand is the theme of teaching and learning with a percentage score of 47%, 2) The research method in demand is Research and Development with a percentage score of 31%, 3) Interesting research subjects are learners with a percentage score of 58%, 4) The data collection technique in demand is a questionnaire with a percentage score of 36%, and 5) The data analysis technique of interest is descriptive statistical analysis with a percentage score of 67%.